PERLINDUNGAN HUKUM TENAGA KERJA DI KOPERASI BONGKAR MUAT PELABUHAN TENAU KUPANG BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Dena, Stefania M; Mauritsius, Darius; Pello, Helsina Fransiska (Petitum Law Journal, 2025)
The objective of this research is to examine the legal protection afforded to the welfare and safety of loading and unloading workers (TKBM) in the TKBM Cooperative of Tenau Port Kupang, and the obstacles experienced in its implementation. Empirical legal research methodology is employed, whereby applicable legal provisions are analysed alongside real-time observations of the field. The findings of this research indicate that the legal protection of TKBM at Tenau Kupang Port is in accordance with Law Number 13 of 2003 concerning Labour. The protection encompasses working time, rest time, work safety, and the provision of Personal Protective Equipment (PPE) to minimise the risk of accidents. However, the implementation of these measures is hindered by several factors. These include wage uncertainty, which is dependent on the frequency of ship arrivals, the wage gap between containers and bulk containers, and a lack of awareness regarding the importance of PPE use. Furthermore, inclement weather, damage to transport equipment, and instances of thuggery pose additional challenges to the protection of TKBM's welfare and safety. Not with standing these challenges, the cooperative has introduced BPJS Employment, which provides work accident insurance and old age insurance for workers.as the ‘milk fallacy’ or if it will change the face of the case law as it currently stands.